Использование устройства активных потерь для расширения диапазона технических характеристик при измерении параметров вибрации - Руженцев, И. В.; Потыльчак, А. П.; Жопткевич, Е. И. (НТУ "ХПИ", 2008)
Розглянуті проблеми контролю параметрів вібрації при оцінці технічного стану й ресурсу надійності роторних машин. Проведений аналіз сучасних засобів вимірювальної техніки, використовуваних при калібруванні систем контролю параметрів вібрації. Запропоноване використання пристрою активних втрат як імітатора вібростенда.

Problems of the control of parameters of vibration are considered at an estimation of a technical condition and a resource of reliability of rotors. The analysis of modern means of the measuring technics used at calibration of monitoring systems of parameters of vibration is lead. Use of the device of active losses as the simulator vibration-testing machine is offered.
Keywords: роторные машины; генераторы; снижения вибрации; ресурс надежности; вибрационный контроль; калибровочные вибростенды